2021
DOI: 10.3390/ijms222313163
|View full text |Cite
|
Sign up to set email alerts
|

Neochlorogenic Acid Attenuates Hepatic Lipid Accumulation and Inflammation via Regulating miR-34a In Vitro

Abstract: Neochlorogenic acid (5-Caffeoylquinic acid; 5-CQA), a major phenolic compound isolated from mulberry leaves, possesses anti-oxidative and anti-inflammatory effects. Although it modulates lipid metabolism, the molecular mechanism is unknown. Using an in-vitro model of nonalcoholic fatty liver disease (NAFLD) in which oleic acid (OA) induced lipid accumulation in HepG2 cells, we evaluated the alleviation effect of 5-CQA. We observed that 5-CQA improved OA-induced intracellular lipid accumulation by downregulatin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(10 citation statements)
references
References 52 publications
0
10
0
Order By: Relevance
“…38 39 Urolithin A, carnosic acid and neochlorogenic acid appear to exert their upregulatory impacts on Sirt1 synthesis by suppressing expression of miR-34a, which binds to the 3'UTR of Sirt1 mRNA and promotes its degradation. [40][41][42][43][44][45][46][47] Agents of this type may be of particular interest in cardiovascular medicine, inasmuch as upregulation of miR-34a, in addition to its suppressive effect on Sirt1 expression, works in additional ways to compromise vascular health. 48 Astaxanthin is reported to increase protein expression of Sirt1 in a range of rodent tissues; the mechanism responsible remains unclear.…”
Section: Health Promotion Via Sirtuin 1 Activationmentioning
confidence: 99%
“…38 39 Urolithin A, carnosic acid and neochlorogenic acid appear to exert their upregulatory impacts on Sirt1 synthesis by suppressing expression of miR-34a, which binds to the 3'UTR of Sirt1 mRNA and promotes its degradation. [40][41][42][43][44][45][46][47] Agents of this type may be of particular interest in cardiovascular medicine, inasmuch as upregulation of miR-34a, in addition to its suppressive effect on Sirt1 expression, works in additional ways to compromise vascular health. 48 Astaxanthin is reported to increase protein expression of Sirt1 in a range of rodent tissues; the mechanism responsible remains unclear.…”
Section: Health Promotion Via Sirtuin 1 Activationmentioning
confidence: 99%
“…According to the functionalities, the main phenolic compounds determined in the seeds studied were neochlorogenic, chlorogenic, and protocatechuate acids, which are known to be phenolic compounds with neuroprotective, antibacterial, anti-inflammatory, anti-cancer, anti-diabetic, and hypoallergenic activities [ 65 , 66 , 67 , 68 ]. 2,3-dihydroxybenzoic acid is attributed to present antibacterial properties against the growth of pathogens such as Escherichia coli , Listeria motocytogenes , or Staphylococcus aureus among others; thus, it is widely used against antibiotic resistance [ 69 ].…”
Section: Resultsmentioning
confidence: 99%
“…However, it is expected that the reason why Pectinex only increased the content of 5-CQA and 4-CQA like this can be elucidated through future research. Several studies reported that 5-CQA had an anti-inflammatory effect in brain disease by inhibiting proinflammatory cytokines 56 , high potential for the development of human immunodeficiency virus-1 drug by inhibiting its reverse transcriptase activity 57 , and improved hepatic lipid accumulation and inflammation by regulating miR-34a 58 . In addition, 4-CQA was reported to have antioxidant activity 59 .…”
Section: Discussionmentioning
confidence: 99%